Does volunteering decrease burnout? Healthcare professional and student perspectives on burnout and volunteering - Metzger, Tai; Nguyen, Nathan; Le, Hillary; Havo, Daisy; Ngo, Katherine; Lee, Sebastian; Nguyen, Timmy; Nguyen, Quynhanh; Tran, Leyna; Tong, Nathan; Le, Collin; Dudovitz, Rebecca (Frontiers in Public Health, 2024)
Background Burnout among healthcare providers is a significant crisis in our healthcare system, especially in the context of the COVID-19 pandemic. The aim of this study was to understand what motivates healthcare workers and students to volunteer in their community as well as examine how volunteering relates to burnout. These findings can help health organizations better meet the needs of healthcare workers, as well as provide insights for non-profits that rely on volunteer professionals. Methods Healthcare providers (N = 8), graduate healthcare students (N = 10), and undergraduate students (N = 14) who volunteered at community health fairs completed the OLBI burnout assessment and an individual semi-structured interview to characterize their attitudes toward volunteering and its relationship with burnout. Interviews were recorded, transcribed, and analyzed using a phenomenological approach, comparing themes across levels of burnout among providers and students. Results Participants described that feeling burnt out decreased one’s likelihood to volunteer, but also that volunteering prevented burnout. The OLBI scores showed that 79.2 and 20.8% of students were low and moderately burnt out respectively, and 87.5 and 12.5% of health professionals were low and moderately burnt out, respectively. Students volunteered for professional development while healthcare professionals cited a desire for a change in their day-to-day work as a reason to volunteer. Both students and health professionals often volunteered because they wanted to make a difference, it made them feel good, and/or they felt a responsibility to volunteer. COVID-19 had a wide range of effects on burnout and motivations to volunteer. Conclusion Volunteering may be useful for preventing burnout among healthcare workers and students, but may not be helpful for those already experiencing burnout. Interview responses and the fact that none of the volunteers had high burnout levels according to their OLBI scores suggest those who choose to volunteer may be less burnt out. Healthcare organizations and schools can encourage volunteering by emphasizing the difference healthcare students and professionals can make through volunteering in the community. Increasing convenience and emphasizing professional development can help recruit and retain healthcare student volunteers. Highlighting the chance to diversify their scope of practice may help recruit and retain healthcare professional volunteers.